STIMULATING YOU TO SPEAK; A STRIP STORY AS A TECHNIQUE IN TEACHING SPEAKING - Abdul Aziz Rifa’at (Elite : English and Literature Journal, 2018)
A strip story is one of the techniques that could stimulate the students to speak during the learning process especially in speaking class. The aim of this study was to find out the significance difference of students’ speaking achievement after they were taught by using strip story technique. The pre experimental study was the method of the study. The one group pretest-posttest design approach was used in this study. The study was conducted to sixth semester S1 Nursing students at STIK Siti Khadijah Palembang. The population of the study was all fourth semester S1 Nursing students at STIK Siti Khadijah Palembang in 2018. The total number of the population was 69 students. The sample of the study was 22 fourth semester S1 Nursing students at STIK Siti Khadijah Palembang in 2018. Systematic sampling was used to collect the sample. The test was administered twice as pre-test and post-test. The results of the tests were analyzed by using t-test through SPSS (Statistical Package for Social Sciences) program. The result of the study showed that there was a significant difference in speaking achievement before and after applying strip story technique based on paired sample t-test. Keywords: speaking, strip story Abstrak Strip story adalah sebuah teknik yang dapat merangsang pelajar untuk berbicara selama proses pembelajaran khususnya dalam kelas Speaking. Tujuan dari penelitian ini adalah untuk mencari perbedaan yang signifikan dalam pencapaian kemampuan berbiacra setelah mereka diajarkan menggunakan teknik strip story. Pre-eksperimental adalah metode dalam penelitian ini. Pendekatan yang digunakan adalah one-group pre-test post-test. Penelitian ini dilakukan terhadap mahasiswa semester 6 program studi S1 Keperawatan diSTIK Siti Khadijah Palembang pada tahun 2018. Jumlah populasi dalam penelitian ini adalah 69 mahasiswa. Sampel dalam penelitian ini berjumlah 22 mahasiswa semester empat program studi S1 Keperawatan STIK Siti Khadijah Palembang tahun 2018. Teknik pengambilan sampel meggunakan teknik sistematik. Tes diberikan dua kali berupa pre-test dan post-test. hasil penelitian dianalisa menggunakan t-test dengan program SPSS. Hasil dari tes menunjukkan bahwa terdapat perbedaan yang signifikan dalam pencapaian kemampuan berbicara sebelum dan sesudah diterapkan strip story berdasarkan paired sample t-test.    Kata Kunci: percakapan, cerita acak